Autoimmunity/inflammation in a monogenic primary immunodeficiency cohort. Issue 9 (15th September 2017) - Rae, William; Ward, Daniel; Mattocks, Christopher J; Gao, Yifang; Pengelly, Reuben J; Patel, Sanjay V; Ennis, Sarah; Faust, Saul N; Williams, Anthony P
Abstract : Primary immunodeficiencies (PIDs) are rare inborn errors of immunity that have a heterogeneous phenotype that can include severe susceptibility to life‐threatening infections from multiple pathogens, unique sensitivity to a single pathogen, autoimmune/inflammatory (AI/I) disease, allergies and/or malignancy. We present a diverse cohort of monogenic PID patients with and without AI/I diseases who underwent clinical, genetic and immunological phenotyping. Novel pathogenic variants were identified in IKBKG, CTLA4, NFKB1, GATA2, CD40LG and TAZ as well as previously reported pathogenic variants in STAT3, PIK3CD, STAT1, NFKB2 and STXBP2 . AI/I manifestations were frequently encountered in PIDs, including at presentation. Autoimmunity/inflammation was multisystem in those effected, and regulatory T cell (Treg) percentages were significantly decreased compared with those without AI/I manifestations. Prednisolone was used as the first‐line immunosuppressive agent in all cases, however steroid monotherapy failed long‐term control of autoimmunity/inflammation in the majority of cases and additional immunosuppression was required. Patients with multisystem autoimmunity/inflammation should be investigated for an underlying PID, and in those with PID early assessment of Tregs may help to assess the risk of autoimmunity/inflammation. Primary immunodeficiency disease: Autoimmunity and inflammation common: Patients with rare hereditary disorders of the immune system often experience autoimmunity or inflammation across multiple organ systems. Researchers in the UK, led by William Rae?from University Hospital Southampton, examined 16 patients with primary immunodeficiency diseases caused by single gene defects. They identified several novel and previously reported pathogenic mutations. Nine of the patients had autoimmune‐ or inflammation‐related problems that required steroid treatment. However, these drugs did not work long‐term and the patients required other immune‐suppressing therapies. Analyses of the immune system found that patients with autoimmunity or inflammation had significantly fewer regulatory T cells than control subjects without these symptoms. The finding raises the possibility of testing individuals with primary immunodeficiency diseases for levels of regulatory T cells in order to identify those at greatest risk of autoimmune‐ or inflammation‐associated complications.